The worries and joys of the Galician peasant family at the turn of the 19th and 20th centuries as presented in memoir research - Dolata, Elżbieta (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
The life of Galician families was described in many memoirs, diaries or autobiographies. These sources constituted the basis for at attempt to depict the everyday life of peasant families, which were predominant in Galicia social structure at the turn of the 19th and 20th centuries. The material subject of the analysis comprised peasant memoir publications and the objective was to find out what habits, duties, worries and joys were typical of the Galician people and, to evaluate them with respect to the opportunities and threats for the family at that time. Peasant literature appears to be a precious sourceof documents that show the changes occurring over the years in the Galician villages. The authors of the texts, who not only witness various events but also participate in them, go back to their earlies memories, which gives an idea of what constituted the characteristics of people’s life at that time.
Keywords: history of upbringing; family; Galicia; 19th century; 20th century; education history